A Flexible R-D-Based Multiple Description Scheme for JPEG 2000 - Baccaglini, E.; Tillo, T.; Olmo, G. (IEEE signal processing letters, 2007)
Multiple description coding (MDC) is a good way to combat packet losses in error-prone networks subject to packet erasures. However, redundancy tuning is often difficult, and this makes the generation of descriptions with good redundancy-rate-distortion performance a hard job. Moreover, the complexity of generating more than two descriptions represents a strong limitation to MDC. In this letter, we propose a method that exploits the data rate-distortion characteristics to generate multiple descriptions for JPEG 2000 with tunable redundancy levels. The identification of the best number of descriptions as a function of the network conditions is also addressed